Analisis Faktor yang Berpengaruh dalam Pengambilan Keputusan Investasi pada Mahasiswa Akuntansi UPN “Veteran” Jawa Timur - Devina Setya Vanessa; Muslimin (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to test data and prove the influence of mental accounting, financial literacy, and risk perception on investment decisions of accounting students at the Universitas Pembangunan Nasional "Veteran" Jawa Timur. Method: This research is a research that uses a quantitative approach. The population of this study was accounting students at the National Development University "Veteran" East Java, graduating from the 2020-2023 intake. A sample size of 92 students was used. Sampling was conducted using a random sampling technique calculated using the Slovin formula. Data collection involved an online questionnaire. Data analysis used the PLS-SEM method with SmartPLS 4.0 software. Finding: The research results show that financial literacy and risk perception have a positive influence on investment decisions. Meanwhile, mental accounting has no positive effect on investment decisions. Novelty: The respondents of this study took accounting students as an update of previous research considering the urgency of accounting students inseparable from the world of finance, investment, and its risks.